Emotional Intelligence At Work - Kaur, Kanwalpreet; Singh , Dalip (Gyan Management Journal, 2007)
Emotional Intelligence At Work is a comprehensive book that provides an overall understanding of emotional intelligence to professionals. It is authored bj’ .Dalip Singh and is published by Response Books, A division of Sage Publicatwn, New Delhi. This book is an essential guide to identifying, understanding, using and managing emotions. The target audience for this book is a variety of professionals like business executives academicians, social worker, counsellors, administrators and even students who wish to increase their effectiveness in their professional lives. There are a total of 10 chapters covering just over 296 pages. All the chapters are again divided into different parts to make it effective. In each sub part the author discusses different psychological aspects related to emotional intelligence and explains with the help of examples. In Emotional Intelligence At Work, Dalip Singh introduces two terms "Intelligence Quotient" denoting IQ and ’’Emotional Quotient’’ denoting EQ that is used interchangeably with "Emotional Intelligence". He conducted research on the subject that shows people with high emotional intelligence are happier, healthier and more successful. Having awareness of their own feelings, they are able to strike a balance between reason and emotions, which make them good leader and team player.